Effect of high-moisture grain on availability of phosphorus for swine - M Trotter; G Allee (Kansas Agricultural Experiment Station Research Reports, 1979)
A feeding trial and two phosphorus balance studies were conducted to compare the availabilities of phosphorus from high-moisture sorghum grain treated with propionic acid (1.2% acid, 23% moisture), grain stored in an oxygen limiting structure (27% moisture), and field-dried sorghum grain (13% moisture). Bone and phosphorus retention data indicated that the phosphorus in high-moisture sorghum grain is more available than phosphorus in field-dried sorghum grain.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; High-moisture grain; Phosphorus